Case report: Two case reports of cryptogenic brain abscess caused by Fusobacterium nucleatum and literature review - Zhang, Zuoxin; Liu, Jing; Su, Linxi; Huang, Weiwei; Pei, Yuchun; Huang, Guohao; Yang, Lin; Lv, Shengqing; Yin, Jinbo; Liu, Guolong (Frontiers in Neuroscience, 2023)
Brain abscess originates from a localized cerebritis area of brain parenchyma, remaining a refractory infectious disease in central nervous system. Causative pathogens could be wide-ranged including bacteria, fungi or parasites, thus the precise pathogen identification and individualized antimicrobial therapy determine patients' outcomes. Here, we reported two cases that both patients were only presented with limb dysfunction, but without symptoms, signs, and biological evidence of infection.Samples were obtained through brain stereoscopic surgeries and microbial identifications were performed to confirm the infection of Fusobacterium nucleatum.Further appropriate treatments were given and the patients recovered well. The patient 1 was a 73-year-old male with a 20-day history of left-sided limbs weakness and the brain MRI showed a space-occupying lesion with a heterogeneously ring-enhancement character in right frontal lobe. This patient underwent puncture biopsy of the lesion with the robot-assisted guidance and confirmed a brain abscess.Empirical antibiotic therapy was given immediately until the pathogen was identified as Fusobacterium nucleatum, thus he received the specific antibiotic therapy with metronidazole and recovered well after treatment. The patient 2 was a 22-year-old female with heart disease history who complained right-sided limbs weakness for nine days. The brain MRI showed a circular enhanced lesion with a thin capsule wall and surrounding edema in left frontal lobe. This patient underwent puncture drainage of the lesion with the robot-assisted guidance and confirmed a brain abscess. Empirical antibiotic therapy was given until the pathogen was identified as Fusobacterium nucleatum and then she also received metronidazole treatment. Her symptoms recovered and the lesion disappeared after 1 month. Hence, we reviewed the diagnosis and treatment of cryptogenic brain abscess caused by Fusobacterium nucleatum, and highlighted that the precise neurosurgical interventions and identification of causative pathogens is crucial for the management of brain abscess.